2011
DOI: 10.1159/000332411
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Inhalation of Milrinone Attenuates Inflammation in Patients Undergoing Cardiac Surgery with Cardiopulmonary Bypass

Abstract: Objectives: The purpose of this study was to evaluate the effect of preoperative inhalation of milrinone on cardiopulmonary bypass (CPB)-related inflammation. Subjects and Methods: A total of 30 patients undergoing cardiac surgery were recruited and randomized for preoperative inhalation of milrinone (Mil group) or normal saline (NS group), respectively. Each group had 15 patients. Their hemodynamic parameters were measured and blood samples were obtained longitudinally. The levels of serum interleukin (IL-6),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
(40 reference statements)
0
25
0
Order By: Relevance
“…Exposure to iMil has been reported in 279 patients in small unblinded trials, 10,11,[13][14][15][16] retrospective analyses, 12,19 in combination with iPGI 2 , 18 and in case reports. [20][21][22][23][24][25][26] One trial involving 21 patients compared iMil (n = 11) with placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to iMil has been reported in 279 patients in small unblinded trials, 10,11,[13][14][15][16] retrospective analyses, 12,19 in combination with iPGI 2 , 18 and in case reports. [20][21][22][23][24][25][26] One trial involving 21 patients compared iMil (n = 11) with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…7 The use of inhaled milrinone (iMil) has been described in several animal 8,9 and human reports. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Compared with its alternatives [i.e., inhaled nitric oxide (iNO) and inhaled prostacyclin (iPGI 2 )], iMil possesses inotropic properties, is less expensive, does not require a complex administration system, and does not have toxic metabolites. Furthermore, contrasted with iPGI 2 , iMil is readily available in most cardiac operating rooms and needs no special preparation.…”
Section: Résumémentioning
confidence: 99%
“…Milrinone is a drug for congestive heart failure, and has both inotropic and vasodilator properties53). Milrinone also has anti-inflammatory effects54). A recent prospective, open-label, randomized controlled study demonstrated that patients who were treated with intravenous milrinone (0.5 µg/kg/min) and intravenous immunoglobulin had a lower 1-week mortality rate compared with patients who were treated with dopamine or dobutamine and intravenous immunoglobulin (18.2% vs. 57.9%)55).…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Murinone when administered with catecholamines has been shown to improve cardiovascular function in volume-resuscitated pédiatrie patients with septic shock (31). It suppresses the production of pro-inflammatory cytokines, such as interleukin (IL)-Iß, IL-6, tumor necrosis factor-a, and matrix metallopeptidase-9, by elevating cyclic adenosine monophosphate levels (14,15,32). It suppresses the production of pro-inflammatory cytokines, such as interleukin (IL)-Iß, IL-6, tumor necrosis factor-a, and matrix metallopeptidase-9, by elevating cyclic adenosine monophosphate levels (14,15,32).…”
Section: Discussionmentioning
confidence: 99%